NURSES' PERFORMANCE IN HEALTHCARE-ASSOCIATED INFECTIONS (HAIs) (CIPEEX, 2025)
Healthcare-associated infections (HAIs) continue to be a challenge for healthcare professionals. The objective of this study was to review the role of nurses in relation to HAIs. An integrative literature review was conducted in six stages according to Souza, Silva, and Carvalho (2010). The study included six scientific articles in observational, prospective cross-sectional, case-control, and experience report studies, which showed a broad role of nurses in the occurrence of HAIs, whether to establish signs of infection, manage protocols, evaluate costs, or develop new tools. It was concluded that nurses' perception of the integration of strategies is crucial to improving patient safety and reducing the impact of infections.
Keywords: Infections; Nursing; Performance; Health quality